The Role of Phosphatases in Nuclear Envelope Disassembly and Reassembly and Their Relevance to Pathologies - Florentin Huguet; Shane Flynn; Paola Vagnarelli (Cells, 2019)
The role of kinases in the regulation of cell cycle transitions is very well established, however, over the past decade, studies have identified the ever-growing importance of phosphatases in these processes. It is well-known that an intact or otherwise non-deformed nuclear envelope (NE) is essential for maintaining healthy cells and any deviation from this can result in pathological conditions. This review aims at assessing the current understanding of how phosphatases contribute to the remodelling of the nuclear envelope during its disassembling and reformation after cell division and how errors in this process may lead to the development of diseases.